The Effectiveness of a 5% Retinoic Acid Peel Combined with Microdermabrasion for Facial Photoaging: A Randomized, Double-Blind, Placebo-Controlled Clinical Trial - Gita Faghihi; Saghi Fatemi-Tabaei; Bahareh Abtahi-Naeini; Amir Hossein Siadat; Giti Sadeghian; Mohammad Ali Nilforoushzadeh; Hamed Mohamadian-shoeili (Dermatology Research and Practice)
Background. Tretinoin has been shown to improve photoaged skin. This study was designed to evaluate the efficacy and tolerability of a 5% retinoic acid peel combined with microdermabrasion for facial photoaging. Materials and Methods. Forty-five patients, aged 35–70, affected by moderate-to-severe photodamage were enrolled in this trial. All patients received 3 sessions of full facial microdermabrasion and 3 sessions of either 5% retinoic acid peel or placebo after the microdermabrasion. Efficacy was measured using the Glogau scale. Patients were assessed at 2 weeks and 1, 2, and 6 months after treatment initiation. Results. The mean ± SD age of participants was 49.55±11.61 years, and the majorities (73.3%) were female. Between 1 month and 2 months, participants reported slight but statistically significant improvements for all parameters (P<0.001). In terms of adverse effects, there were statistically significant differences reported between the 5% retinoic acid peel groups and the control group (P<0.001). The majority of adverse effects reported in the study were described as mild and transient. Conclusion. This study demonstrated that 5% retinoic acid peel cream combined with microdermabrasion was safe and effective in the treatment of photoaging in the Iranian population. This trial is registered with IRCT2015121112782N8.